Isolation of a diazinon-degrading strain Sphingobium sp. DI-6 and its novel biodegradation pathway - Wang, Guangli; Li, Xiang; Zheng, Jiaxin; Li, Xuedong; Bai, Lingling; Yue, Wenlong; Jiang, Li (Frontiers in Microbiology, 2022)
Diazinon is one of the most widely used organophosphate insecticides, one that is frequently detected in the environment. In this study, a diazinon-degrading bacterium, DI-6, previously isolated from diazinon-contaminated soil in China has been subsequently identified as Sphingobium sp. on the basis of its physiological and biochemical characteristics, as well as by virtue of a comparative analysis of 16S rRNA gene sequences. This strain is capable of using diazinon as its sole carbon source for growth, and in liquid culture under optimal conditions (pH 7.0, 30 °C), was able to degrade 91.8% of 100 mg L-1 diazinon over a 60-h interval. During the degradation of diazinon, the following seven metabolites were captured and identified by gas chromatography/mass spectrometry (GC-MS) analysis: diazoxon, diazinon aldehyde, isopropenyl derivative of diazinon, hydroxyethyl derivative of diazinon, diazinon methyl ketone, O-(2-(1-hydroxye thyl)-6-methylpyrimidin-4-yl) O-methyl O-hydrogen phosphorothioate, and O-(6-methyl pyrimidin-4-yl) O, O-dihydrogen phosphorothioate. Based on these metabolites, a novel microbial biodegradation pathway of diazinon by Sphingobium sp. DI-6 is proposed. This research provides potentially useful information for the application of the DI-6 strain in bioremediation of diazinon-contaminated environments.